Phytochemical characteristics, antioxidant, and health properties of roasted and unroasted Algerian argan (Argania spinosa) oil. Issue 5 (25th July 2018) - Ben Mansour, Rim; Ben Slema, Haifa; Falleh, Hanen; Tounsi, Moufida; Kechebar, Mohamed Seif Allah; Ksouri, Riadh; Megdiche‐Ksouri, Wided
Abstract: The aim of this work was to investigate the physicochemical, nutritional and antioxidant properties of traditionally pressed edible (roasted argan kernels) and beauty (unroasted argan kernels) Algerian argan oil. Oxidative stability and the quality of oils (acidity, peroxide index, K232, and K270 ) were slightly affected by roasting process. But, any case, none of the analyzed oils surpassed limits established by Moroccan norms and were labeled as "extra virgin oil." In addition, the better antioxidant capacities of argan oil prepared from roasted seeds could be explained by a better extractability of carotenoids, phenolics. and tocopherols as compared with unroasted ones. The dominant fatty acids found consisted by oleic acid followed by linoleic, palmitic, and stearic acids and the major triglycerides were principally formed by two or three oleic acid residues. According to our data, the roasting process does not influence the quality of the argan oil and confirm its good stability. Practical applications: Argania spinosa ( Sapotaceae family) is an endemic xero‐thermophilic species from the southwestern region of Algeria (Tindouf countryside) and Morocco. Argan oil is the most important products derived from Argan tree. Despite its wide spread uses and properties, only few studies had been carried out on the traditionally extracted roasted (edible) and unroasted (for beauty uses) Algerian argan oil. Thus, this study aimed to valorize this oil through their physicochemical, nutritional and antioxidant properties in order to situate this local product to the standards and international norm values.